2011
DOI: 10.1152/ajplung.00166.2010
|View full text |Cite
|
Sign up to set email alerts
|

PKR-dependent CHOP induction limits hyperoxia-induced lung injury

Abstract: Lozon TI, Eastman AJ, Matute-Bello G, Chen P, Hallstrand TS, Altemeier WA. PKR-dependent CHOP induction limits hyperoxia-induced lung injury. Am J Physiol Lung Cell Mol Physiol 300: L422-L429, 2011. First published December 24, 2010 doi:10.1152 doi:10. /ajplung.00166.2010 is commonly employed in patients with respiratory failure; however, hyperoxia is also a potential contributor to lung injury. In animal models, hyperoxia causes oxidative stress in the lungs, resulting in increased inflammation, edema, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
39
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 43 publications
5
39
2
Order By: Relevance
“…However, BiP protein appeared to be increased in MLE-12 cells (Figures E1A and E1B). On the other hand, we noted a marked increase in CHOP protein ( Figure E1B), as also reported in an earlier study with MLE-12 cells (43). We found that CHOP siRNA decreased cell death in MLE-12 cells ( Figure E2).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, BiP protein appeared to be increased in MLE-12 cells (Figures E1A and E1B). On the other hand, we noted a marked increase in CHOP protein ( Figure E1B), as also reported in an earlier study with MLE-12 cells (43). We found that CHOP siRNA decreased cell death in MLE-12 cells ( Figure E2).…”
Section: Discussionsupporting
confidence: 91%
“…In terms of hyperoxic exposure, an earlier study evaluated MLE-12 cells for 24 hours, and noted little change in BiP mRNA and protein concentrations (43). We noted no change in BiP mRNA.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Although primary AEII cells would be a more accurate model to study O2 in vitro, the yield is often low during the isolation process, thus making analyzing various readouts difficult. However, there have been a few studies that have isolated murine primary AE II cells (40,49,50) with varying O2 exposure times between 24 to 48 hours. Although most described the overall cell survival and proliferation in such settings, none commented on the antioxidant profile associated with their findings.…”
Section: Discussionmentioning
confidence: 99%
“…CHOP is often used as a marker for ER stress activation, and it is a major player in ER stress-triggered apoptosis (36 -38); nevertheless, the ER stress response can be induced independently of CHOP (44). Conversely, CHOP expression can be up-regulated independently of ER stress (45). Therefore, it appears possible that, following suppression of Man2C1 expression, CHOP is somehow up-regulated independently of ER stress.…”
Section: Discussionmentioning
confidence: 99%